THE INFLUENCE OF E-BOOKS ON READING HABIT AND READING COMPREHENSION ACHIEVEMENT OF THE ELEVENTH-GRADERS OF SMA XAVERIUS 1 PALEMBANG - Selly Selly (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2016)
THE INFLUENCE OF E-BOOKS ON READING HABIT AND READING COMPREHENSION ACHIEVEMENT OF THE ELEVENTH-GRADERS OF SMA XAVERIUS 1 PALEMBANG     Selly sellytheng@gmail.com         Abstract: The objectives of this study were to find out whether or not there were significant differences in reading habit and reading comprehension achievement between the eleventh graders who used e-books and those who used printed books,  a significant correlation between reading habit and reading comprehension achievement, and a significant correlation between each aspect of reading habit and each sub-skill of reading comprehension achievement. The results showed that there were significant differences in reading habit and reading comprehension achievement between the eleventh graders who used e-books and those who used printed books. At the significance level of 0.05 and 2 tailed testing, the correlation coefficient showed that the r-obtained (0.301) was higher than r-table (0.115). Therefore, there was a significant correlation between reading habit and reading comprehension achievement. In e-books and non e-books classes, reading attitude was the aspect, which had a strong correlation with almost all sub-skills of reading comprehension achievement. Meanwhile, reading accessed was the aspect, which had no correlation with almost all sub-skills of reading comprehension achievement.   Key words: Reading comprehension Achievement, Reading Habit, E-book